Never take a shark to the dentist : (and other things not to do) - Barrett, Judi.; Nickle, John (New York : Atheneum Books for Young Readers, 2008)
A list of things one should not do with various animals, such as "hold hands with a lobster.".
Kirkus Review
Pub Weekly
2.0
K-3.
K-3
Keywords: Animals -- Juvenile fiction; Animals -- Fiction; Animals -- Fiction